Confronting the Past: The Role of the European Historian Today. (February 2023) - Chabal, Emile; Karamouzi, Eirini
Abstract : The pandemic may have consigned historians to their homes, but this did not stop history from taking centre-stage in public debate. From falling statues to culture wars, history in all its forms has continued to be deployed by states, activists, prestigious institutions and grassroots organisations. As has always been the case, those who study history for a living have rarely played a prominent role in these debates. At best, historians have tended to be confined to supporting roles as 'advisers', 'consultants' or 'experts'. Still, even for those historians who eschew the rough-and-tumble of political and civic discussion, it is impossible to remain entirely neutral. Governments and politicians can overturn funding priorities; universities can suddenly find themselves targets of hostile political campaigning; and lecture halls can turn into sites of civic struggle. This constant historical instrumentalisation is a dramatic reminder of the power of narratives in constructing realities.